Lactotroph PitNET/adenoma associated to granulomatous hypophysitis in a patient with Crohn's disease: A case report. Issue 1 (10th August 2022) - Pietrantoni, Alberto; Serioli, Simona; Cominelli, Manuela; Lodoli, Giovanni; Stefini, Roberto; Villanacci, Vincenzo; Poliani, Pietro Luigi
Abstract : Granulomatous hypophysitis is a rare and poorly understood condition. Although certain cases are treated as primary pituitary autoimmune disorders, rare cases may be associated with pituitary neuroendocrine tumours (PitNETs) and systemic inflammatory diseases. Here, we report a case of a 47‐year‐old man that underwent endoscopic trans‐sphenoidal excision of a pituitary mass diagnosed as PitNET. On histologic evaluation, the neoplasm showed an admixture of granulomas with extensive inflammatory infiltrate and lactotroph PitNET/adenoma. Careful anamnestic examination revealed a diagnosis of Crohn's disease 20 years prior. Although rarely done, both PitNET and Crohn's disease may be associated with granulomatous hypophysitis, and our patient had both conditions. During the 6‐year follow‐up, PitNETs and hypophysitis did not recur, while Crohn's disease was only partially controlled by medical therapy. To our knowledge, this is the first description of association of granulomatous hypophysitis, PitNET and Crohn's disease.